The Impact of Financial Literacy and Employability Skills Development on Corporate Financial Performance - Yadav, Jitendra (Journal of Educational Research and Policies, 2026)
This study examines the role of financial education and employability skills in enhancing corporate financial performance over the last century. By tracing the evolution of corporate training programs, the paper highlights how investments in workforce education have shifted from operational costs to strategic assets. Case studies and historical examples illustrate how financially literate and skilled employees contribute to resilience, innovation, and profitability within organizations. This analysis provides evidence that a combination of financial literacy and employability skills fosters improved decision - making, engagement, and risk management across organizational levels, supporting long - term financial growth.